2013
DOI: 10.1074/jbc.m113.489674
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor γ Coactivator 1 (PGC-1)- and Estrogen-related Receptor (ERR)-induced Regulator in Muscle 1 (PERM1) Is a Tissue-specific Regulator of Oxidative Capacity in Skeletal Muscle Cells

Abstract: Background:The regulatory mechanisms that control skeletal muscle bioenergetics are not fully understood. Results: The muscle-specific protein Perm1 is induced by exercise and exercise-activated regulators and controls the expression of energy homeostasis genes. Conclusion: Perm1 is a regulator of mitochondrial oxidative capacity and bioenergetics. Significance: Novel muscle regulators of bioenergetics may facilitate approaches for preserving/enhancing muscle function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
106
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 70 publications
8
106
2
Order By: Relevance
“…In previous studies, we found that Perm1 was required for the induction of mitochondrial biogenesis by PGC1a in cultured myotubes (32). Thus, we next assessed the effect of increased Perm1 expression on skeletal muscle mitochondrial content and oxidative activity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, we found that Perm1 was required for the induction of mitochondrial biogenesis by PGC1a in cultured myotubes (32). Thus, we next assessed the effect of increased Perm1 expression on skeletal muscle mitochondrial content and oxidative activity.…”
Section: Resultsmentioning
confidence: 99%
“…Differentiated myotubes were infected on d 4 of differentiation with adenoviruses expressing LacZ (control) or Perm1 at multiplicity of infection 50 (32). Cells were harvested 24 h after infection.…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations